Under Representation of the Inhibitory KIR3DL1 Molecule and the KIR3DL1+/BW4+ Complex in HIV Exposed Seronegative Individuals - Guerini, Franca Rosa (Oxford University Press, 2011)
The activation of natural killer (NK) cells is modulated by surface molecules. We analyzed NK cells in human immunodeficiency virus (HIV)–exposed seronegative (HESN) individuals by means of molecular typing of HLA B, Cw, and killer cell immunoglobulin-like receptor (KIR) molecules. In HESN individuals, compared with HIV patients, the frequency of the inhibitory KIR3DL1 allele and of the KIR3DL1(+)/Bw4(+) inhibitory complex was reduced, whereas that of the activatory KIR3DS1(+) ligand and the activatory Bw4(+)/3DL1(–)/3DS1(+) complex was increased, resulting in a statistically significant diversion from Hardy-Weinberg equilibrium (KIR3DS1 homozygote) in HESN individuals. The reciprocal equilibrium between inhibitory and activatory NK receptors and their ligands favors NK activation in HESN individuals.